Integration of geotechnical parameters and infrastructure preparedness policy in disaster mitigation in earthquake-prone areas - Arissa Sabilla (Calamity: A Journal of Disaster Technology and Engineering, 2026)
Background: This study investigates the geotechnical characteristics and seismic response of soils, which lies near the active Seulimum Fault. The research aims to analyze soil behavior under seismic influences through laboratory testing and theoretical calculations. Laboratory tests included determining water content, specific gravity, grain size distribution, and Atterberg limits to classify soil types and evaluate their physical properties. The study also analyzed earthquake acceleration and uplift forces to assess the dynamic response of the soil. Methods: Soil samples were collected from a depth of 10 meters and analyzed for moisture content, specific gravity, particle size distribution, and Atterberg limits to determine their geotechnical properties. Earthquake-induced ground acceleration and uplift forces were then calculated to assess soil behavior under seismic loading. All tests followed standard ASTM procedures to ensure reliable and comparable results. Findings: Results showed that the soil has an average specific gravity of 2.619 and a plasticity index of 38.42%, indicating a highly plastic clay (CH) with low shear strength and high swelling potential. The maximum ground acceleration reached 0.00236 g, while uplift force increased from 0.82 kg to 7.47 kg over 96 hours, suggesting rising pore-water pressure that can reduce effective stress and stability. Conclusion: The findings emphasize the importance of integrating geotechnical results into spatial planning and disaster mitigation policies. This study provides novel insights into linking soil mechanics and seismic risk assessment for infrastructure resilience in earthquake-prone zones. Novelty/Originality of this article: This study provides novel insights by integrating laboratory-based geotechnical analysis with seismic response modeling to evaluate soil behavior near an active fault, offering practical guidance for infrastructure resilience and disaster mitigation in earthquake-prone areas.